Pendampingan Usaha Air Minum Masjid Sebagai Model Pemberdayaan Ekonomi Jamaah: Program Pelatihan Di Masjid Attaqwa Sukaraya Indah - Syuhada, Wira; Hamdan 'Ainulyaqin, Muhammad (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2025)
This article describes the implementation of a drinking water business mentoring program at the Attaqwa Sukaraya Indah Mosque, Karang Bahagia District, Bekasi Regency, West Java Province as a model for empowering the congregation's economy. This study describes the training process, development, and results achieved in an effort to improve the congregation's economic welfare through the mosque's drinking water business. Data shows a significant increase in network development and financial management from 2021 to 2024. This program is a model for sustainable mosque-based economic empowerment, with a total balance reaching IDR 20,136,887 during that period. This empowerment model can be an example for other mosques in developing productive economic programs based on local potential.